2021
DOI: 10.1093/function/zqab041
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke Exposure Impairs Ion Channel Function and Contractility of Mesenteric Arteries

Abstract: Cigarette smoke, including secondhand smoke (SHS), has significant detrimental vascular effects, but its effects on myogenic tone of small resistance arteries and the underlying mechanisms are understudied. Although it is apparent that SHS contributes to endothelial dysfunction, much less is known about how this toxicant alters arterial myocyte contraction, leading to alterations in myogenic tone. The study's goal is to determine the effects of SHS on mesenteric arterial myocyte contractility and excitability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…We used a modified PLA validated by us and others to examine α1 C oligomerization/clustering. 46 , 47 A similar modified PLA has been used to examine oligomerization/clustering of epidermal growth factor receptors and α-synuclein. 48 , 49 In our modified PLA, a single α1 C monoclonal antibody is labeled with the PLUS or MINUS probe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a modified PLA validated by us and others to examine α1 C oligomerization/clustering. 46 , 47 A similar modified PLA has been used to examine oligomerization/clustering of epidermal growth factor receptors and α-synuclein. 48 , 49 In our modified PLA, a single α1 C monoclonal antibody is labeled with the PLUS or MINUS probe.…”
Section: Resultsmentioning
confidence: 99%
“…The modified PLA assay ( Figure S4A and 46 , 47 ) showed that PLA puncta density was significantly elevated in WT but not S1928A, STZ arterial myocytes compared with WT/S1928A sham cells (Figure 6 A, Table S11 ). No PLA signal was observed when the primary antibody was omitted ( Figure S5A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Freshly isolated mesenteric artery segments were mounted in a 5‐mL myograph chamber to determine arterial diameter changes in response to changes in intraluminal pressure as previously described. 27 …”
Section: Methodsmentioning
confidence: 99%
“…In this issue's article, “Secondhand Smoke Exposure Impairs Ion Channel Function and Contractility of Mesenteric Arteries,” 3 Le et al . provide elegant inroads into this question.…”
Section: A Perspective On “Secondhand Smoke Exposure Impairs Ion Chan...mentioning
confidence: 99%